2014
DOI: 10.17221/360/2013-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cow energy status on the hypercholesterolaemic fatty acid proportion in raw milk

Abstract: Ducháček J., Stádník L., Ptáček M., Beran J., Okrouhlá M., Čítek J., Stupka R. (2014): Effect of cow energy status on the hypercholesterolaemic fatty acid proportion in raw milk. Czech J. Food Sci., 32: 273-279.We evaluated the proportion of fatty acid groups, with an emphasis on hypercholesterolaemic fatty acids, in the milk of 25 Holstein cows during the 1 st period of lactation in relation to their negative energy balance (NEB). Sampling of each cow's milk started on the 7 th day after calving. Milk samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
6
13
0
1
Order By: Relevance
“…Wolfová et al, 2007;Ducháček et al, 2014). Contents of SFAs, MUFAs and PUFAs determined in our study are within the range that has been recently reported for these FA groups in H and CF cows (Samková et al, 2014;Stádník et al, 2013;Ducháček et al, 2014). As mentioned earlier, breed belongs to factors affecting FA composition of milk fat, as proved in recent studies (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Wolfová et al, 2007;Ducháček et al, 2014). Contents of SFAs, MUFAs and PUFAs determined in our study are within the range that has been recently reported for these FA groups in H and CF cows (Samková et al, 2014;Stádník et al, 2013;Ducháček et al, 2014). As mentioned earlier, breed belongs to factors affecting FA composition of milk fat, as proved in recent studies (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…NEFA levels can be increased through increased mobilization of stored lipids, which can thereby indicate metabolic disorders, such as ketosis and fatty liver syndrome (Duffield et al, 1998;Fiore et al, 2017). The first measurable indicator of ketogenesis is an increase in BHB concentration in the blood (Payne and Payne, 1987;Schulz et al, 2014) The utilization of energy reserves is also reflected in the milk fat content (Bauman et al, 2006), namely in the fatty acid (FA) composition and mutual ratios between individual FA groups (Ducháček et al, 2014). Milk FA and protein contents are correlated with metabolic status (Mulligan et al, 2006); therefore, measurement of these two parameters is usually recommended for the determination of negative energy balance (Gross et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Milk composition is affected in general by genotype (Stádník et al, 1999; K adlecová et al, 2014), feeding system and nutrition level (Rego et al, 2009), systems of milking (Bobić et al, 2013), morphology of teat and udder (Szencziová et al, 2013) as well as other factors. The milk fat is a key component of raw milk determining energy balance of cows (K adlecová et al, 2014) as well as processing, technological, and nutritional quality of milk (Ducháček et al, 2014). It is also one of the most variable parts of raw milk at the same time .…”
Section: Introductionmentioning
confidence: 99%